Safety and immunogenicity of RV3-BB human neonatal rotavirus vaccine administered at birth or in infancy: a randomised, double-blind, placebo-controlled trial. Issue 12 (December 2015) - Bines, Julie E; Danchin, Margaret; Jackson, Pamela; Handley, Amanda; Watts, Emma; Lee, Katherine J; West, Amanda; Cowley, Daniel; Chen, Mee-Yew; Barnes, Graeme L; Justice, Frances; Buttery, Jim P; et al.
Summary: Background: Despite the success of rotavirus vaccines, suboptimal vaccine efficacy in regions with a high burden of disease continues to present a challenge to worldwide implementation. A birth dose strategy with a vaccine developed from an asymptomatic neonatal rotavirus strain has the potential to address this challenge and provide protection from severe rotavirus disease from birth. Methods: This phase 2a randomised, double-blind, three-arm, placebo-controlled safety and immunogenicity trial was undertaken at a single centre in New Zealand between Jan 13, 2012, and April 17, 2014. Healthy, full-term (≥36 weeks gestation) babies, who weighed at least 2500 g, and were 0–5 days old at the time of randomisation were randomly assigned (1:1:1; computer-generated; telephone central allocation) according to a concealed block randomisation schedule to oral RV3-BB vaccine with the first dose given at 0–5 days after birth (neonatal schedule), to vaccine with the first dose given at about 8 weeks after birth (infant schedule), or to placebo. The primary endpoint was cumulative vaccine take (serum immune response or stool shedding of vaccine virus after any dose) after three doses. The immunogenicity analysis included all randomised participants with available outcome data. This trial is registered with the Australian New Zealand Clinical Trials Registry, ACTRN12611001212943. Findings: 95 eligible participants were randomised, of whom 89 were included in the primary analysis. A cumulative vaccine take was detected in 27 (90%) of 30 participants in the neonatal schedule group after three doses of RV3-BB vaccine compared with four (13%) of 32 participants in the placebo group (difference in proportions 0·78, 95% CI 0·55–0·88; p<0·0001). 25 (93%) of 27 participants in the infant schedule group had a cumulative vaccine take after three doses compared with eight (25%) of 32 participants in the placebo group (difference in proportions 0·68, 0·44–0·81; p<0·0001). A serum IgA response was detected in 19 (63%) of 30 participants and 20 (74%) of 27 participants, and stool shedding of RV3-BB was detected in 21 (70%) of 30 participants and 21 (78%) of 27 participants in the neonatal and infant schedule groups, respectively. The frequency of solicited and unsolicited adverse events was similar across the treatment groups. RV3-BB vaccine was not associated with an increased frequency of fever or gastrointestinal symptoms compared with placebo. Interpretation: RV3-BB vaccine was immunogenic and well tolerated when given as a three-dose neonatal or infant schedule. A birth dose strategy of RV3-BB vaccine has the potential to improve the effectiveness and implementation of rotavirus vaccines. Funding: Australian National Health and Medical Research Council, the New Zealand Health Research Council, and the Murdoch Childrens Research Institute.